Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To solve the equation [tex]\(4 + \frac{3}{x - 2} = \frac{3}{x - 3}\)[/tex], let's follow a step-by-step process.
1. Move the constants and fractions to one side:
[tex]\[4 + \frac{3}{x - 2} = \frac{3}{x - 3}\][/tex]
2. Isolate the term with fractions:
[tex]\[\frac{3}{x - 2} - \frac{3}{x - 3} = -4\][/tex]
3. Factor out the common factor [tex]\(3\)[/tex] in the numerators:
[tex]\[3\left(\frac{1}{x - 2} - \frac{1}{x - 3}\right) = -4\][/tex]
4. Combine the fractions on the left-hand side:
[tex]\[3 \left( \frac{(x - 3) - (x - 2)}{(x - 2)(x - 3)} \right) = -4\][/tex]
Simplify the numerator:
[tex]\[3 \left( \frac{x - 3 - x + 2}{(x - 2)(x - 3)} \right) = -4\][/tex]
[tex]\[3 \left( \frac{-1}{(x - 2)(x - 3)} \right) = -4\][/tex]
5. Simplify the expression:
[tex]\[\frac{-3}{(x - 2)(x - 3)} = -4\][/tex]
6. Eliminate the negative signs by multiplying both sides by [tex]\(-1\)[/tex]:
[tex]\[\frac{3}{(x - 2)(x - 3)} = 4\][/tex]
7. Cross-multiply to solve for [tex]\(x\)[/tex]:
[tex]\[3 = 4(x - 2)(x - 3)\][/tex]
8. Divide both sides by 4 to isolate [tex]\(x\)[/tex]:
[tex]\[\frac{3}{4} = (x - 2)(x - 3)\][/tex]
9. Expand the product on the right side:
[tex]\[\frac{3}{4} = x^2 - 5x + 6\][/tex]
10. Multiply both sides by 4 to clear the fraction:
[tex]\[3 = 4x^2 - 20x + 24\][/tex]
11. Rearrange the equation to form a standard quadratic equation:
[tex]\[4x^2 - 20x + 24 - 3 = 0\][/tex]
[tex]\[4x^2 - 20x + 21 = 0\][/tex]
12. Use the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex], where [tex]\(a = 4\)[/tex], [tex]\(b = -20\)[/tex], and [tex]\(c = 21\)[/tex].
Calculate the discriminant:
[tex]\[b^2 - 4ac = (-20)^2 - 4(4)(21)\][/tex]
[tex]\[= 400 - 336\][/tex]
[tex]\[= 64\][/tex]
Solve for [tex]\(x\)[/tex]:
[tex]\[x = \frac{-(-20) \pm \sqrt{64}}{2 \cdot 4}\][/tex]
[tex]\[x = \frac{20 \pm 8}{8}\][/tex]
Find the two solutions:
[tex]\[x = \frac{20 + 8}{8} = \frac{28}{8} = \frac{7}{2}\][/tex]
[tex]\[x = \frac{20 - 8}{8} = \frac{12}{8} = \frac{3}{2}\][/tex]
Therefore, the solutions to the equation [tex]\(4 + \frac{3}{x - 2} = \frac{3}{x - 3}\)[/tex] are [tex]\(x = \frac{3}{2}, \frac{7}{2}\)[/tex].
1. Move the constants and fractions to one side:
[tex]\[4 + \frac{3}{x - 2} = \frac{3}{x - 3}\][/tex]
2. Isolate the term with fractions:
[tex]\[\frac{3}{x - 2} - \frac{3}{x - 3} = -4\][/tex]
3. Factor out the common factor [tex]\(3\)[/tex] in the numerators:
[tex]\[3\left(\frac{1}{x - 2} - \frac{1}{x - 3}\right) = -4\][/tex]
4. Combine the fractions on the left-hand side:
[tex]\[3 \left( \frac{(x - 3) - (x - 2)}{(x - 2)(x - 3)} \right) = -4\][/tex]
Simplify the numerator:
[tex]\[3 \left( \frac{x - 3 - x + 2}{(x - 2)(x - 3)} \right) = -4\][/tex]
[tex]\[3 \left( \frac{-1}{(x - 2)(x - 3)} \right) = -4\][/tex]
5. Simplify the expression:
[tex]\[\frac{-3}{(x - 2)(x - 3)} = -4\][/tex]
6. Eliminate the negative signs by multiplying both sides by [tex]\(-1\)[/tex]:
[tex]\[\frac{3}{(x - 2)(x - 3)} = 4\][/tex]
7. Cross-multiply to solve for [tex]\(x\)[/tex]:
[tex]\[3 = 4(x - 2)(x - 3)\][/tex]
8. Divide both sides by 4 to isolate [tex]\(x\)[/tex]:
[tex]\[\frac{3}{4} = (x - 2)(x - 3)\][/tex]
9. Expand the product on the right side:
[tex]\[\frac{3}{4} = x^2 - 5x + 6\][/tex]
10. Multiply both sides by 4 to clear the fraction:
[tex]\[3 = 4x^2 - 20x + 24\][/tex]
11. Rearrange the equation to form a standard quadratic equation:
[tex]\[4x^2 - 20x + 24 - 3 = 0\][/tex]
[tex]\[4x^2 - 20x + 21 = 0\][/tex]
12. Use the quadratic formula [tex]\(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\)[/tex], where [tex]\(a = 4\)[/tex], [tex]\(b = -20\)[/tex], and [tex]\(c = 21\)[/tex].
Calculate the discriminant:
[tex]\[b^2 - 4ac = (-20)^2 - 4(4)(21)\][/tex]
[tex]\[= 400 - 336\][/tex]
[tex]\[= 64\][/tex]
Solve for [tex]\(x\)[/tex]:
[tex]\[x = \frac{-(-20) \pm \sqrt{64}}{2 \cdot 4}\][/tex]
[tex]\[x = \frac{20 \pm 8}{8}\][/tex]
Find the two solutions:
[tex]\[x = \frac{20 + 8}{8} = \frac{28}{8} = \frac{7}{2}\][/tex]
[tex]\[x = \frac{20 - 8}{8} = \frac{12}{8} = \frac{3}{2}\][/tex]
Therefore, the solutions to the equation [tex]\(4 + \frac{3}{x - 2} = \frac{3}{x - 3}\)[/tex] are [tex]\(x = \frac{3}{2}, \frac{7}{2}\)[/tex].
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.